Consumers' food control risk attitude for blockchain traceable information seeking: Evidence from fresh fruit buyers in China - Zhai, Qianqian; Sher, Ali; Li, Qian; Chen, Chao (Frontiers in Sustainable Food Systems, 2022)
The blockchain-based traceability in agri-food marketing has brought a disruptive paradigm shift by removing the inherent information asymmetry problem. Likewise, revealing sufficient product quality and attributes information could break agricultural markets' “Lemon Market” dilemma. This study takes the fresh fruit with blockchain traceability QR label as a case and systematically investigates the influence of consumers' food control risk attitude on information-seeking intentions. We utilized online survey data of 1,058 fresh fruit buyers and simultaneously applied ordinary least square (OLS), ordered logit model (Ologit), and propensity score matching (PSM) approaches to overcome the potential self-selection biases and confounding factors. The results show that risk attitude significantly negatively impacts consumers' information seeking fresh fruits. The stronger consumers' risk preference, the lower the probability of information seeking. Furthermore, we used PSM to overcome potential sample selectivity bias; therefore, PSM reinforces the significance of OLS and Ologit results. The sub-sample estimation results show that young individuals with high school and below education have stronger blockchain information-seeking intentions. The study provides new insights into the role of food control risk attitude and agri-food information traceability and offers several measures for policy and practice to realize a border trajectory in agri-food information disclosure.